Visualization features of canalis sinuosus with cone beam computed tomography - Yuri G Sedov; Anatoly M Avanesov; Oleg S Mordanov; Dina D Zurnacheva; Rita S Mustafaeva; Anastasia V Blokhina (Wolters Kluwer Medknow Publications, 2019)
Introduction: One of the key stages of evaluating an edentulous ridge prior to dental implant placement is the analysis of neighboring anatomical structures such as canalis sinuosus (CS) with cone-beam computed tomography (CBCT). CBCT visualization has its own features, such as the change of slice thickness. The aim of the study was to analyze CS prevalence in relation to the slice thickness and CS diameter according to CBCT scans. Materials and Methods: In total, 100 CBCT scans of 39 males and 61 females in the age span of 46 to 81 years were retrospectively studied. Terminal alveolar part of CS was analyzed in Ez3D2009 (Vatech) software on panoramic and cross-sectional views with 0.5 mm, 1 mm, 3 mm, and 10 mm slice thicknesses. The prevalence was documented with regard to the diameter and slice thickness and was statistically compared in age and gender groups. Results: This CBCT study demonstrated 55.5% CS prevalence. There was no statistically significant difference in presence between age and gender groups regarding diameter as well as within different slice thickness. The study also showed the importance of the slice thickness choice for CS visualization: the best visualization was reached with 0.5 mm and 1 mm slice thicknesses. Visualization with 0.5 mm and 1 mm slice thicknesses was absolutely the same (55.5%). General CS prevalence with a 10 mm slice thickness (16.5%) was significantly lower (P < 0.05) than the prevalence with a 3 mm slice thickness (20.5%). The correlation between the slice thickness and a diameter more than 1.5 mm in size was not found. Conclusion: CBCT analysis showed that the highest CS prevalence was detected with the use of 0.5/1 mm slice thickness. As well, the higher CS diameter, the better is its visualization.